2005
DOI: 10.1016/j.jalz.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of Alzheimer's disease with high folate intake: The Baltimore Longitudinal Study of Aging

Abstract: Background-Study findings have suggested an association between Alzheimer's disease (AD) risk and several vitamins and have speculated about their use as preventive agents. Here, we examine whether total intake (intake from diet plus supplements) of antioxidant vitamins (E, C, carotenoids) and B vitamins (folate, B 6 , and B 12 ) is associated with a reduced risk of AD.Methods-Participants were 579 nondemented elderly volunteers from the Baltimore Longitudinal Study of Aging who completed dietary diaries and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 45 publications
(51 reference statements)
7
74
1
Order By: Relevance
“…In contrast, the studies that examined the association of vitamin B 12 with AD were null (159,(176)(177)(178)(180)(181)(182) . There have been a number of randomised trials of the effects of supplementation with folic acid and vitamin B 12 on cognitive decline.…”
Section: B-vitamins Cognitive Decline and Alzheimer's Diseasementioning
confidence: 96%
“…In contrast, the studies that examined the association of vitamin B 12 with AD were null (159,(176)(177)(178)(180)(181)(182) . There have been a number of randomised trials of the effects of supplementation with folic acid and vitamin B 12 on cognitive decline.…”
Section: B-vitamins Cognitive Decline and Alzheimer's Diseasementioning
confidence: 96%
“…For example, the e4 allele of the Apolipoprotein E gene (APOE) has emerged as a clear genetic susceptibility factor for Alzheimer's dementia [8], although it has not resulted in effective therapeutic strategies, thus far. Numerous observational studies have reported putative protective effects in relation to dietary intake and nutritional supplementation (fish oils [9], folate [10] and vitamins E and C [11]); mental [12] and physical exercise [13]; and medications including estrogen therapy [14], non-steroidal anti-inflammatory drugs [15], and statins [16]. Unfortunately, the limited randomized clinical trials to date have not supported a role for these agents in the prevention of AD [17,18], but more studies need to be done.…”
Section: Risk and Preventive Factors And The Public Health Impact Of mentioning
confidence: 99%
“…High folate intake was associated with reduced risk of developing AD in the Baltimore Longitudinal Study of Aging (Corrada et al, 2005), but there was no association with vitamin supplement and/or food intake of folate in the Chicago Health and Aging Project (CHAP) study (Morris et al, 2006a). In both studies, no association was found with total intake of vitamins B12 or B6.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, there are a limited number of prospective cohort studies on B vitamins and dementia, and the findings have not been consistent. Very few prospective studies examined the levels of B vitamins and Hcy in relation to incidence of dementia (Luchsinger et al, 2004;Corrada et al, 2005;Ravaglia et al, 2005;Morris et al, 2006b;Luchsinger et al, 2007b;Wald et al, 2011).…”
Section: Introductionmentioning
confidence: 99%